Creating Partnerships to Achieve Health Care Reform: Moving Beyond a Politics of Scale?. (January 2019) - Hanlon, Neil; Reay, Trish; Snadden, David; MacLeod, Martha
This article critically exams efforts to achieve primary health care reform using a consultative and relationship-building approach. The study is set in a predominantly rural region of British Columbia, Canada, and concerns the efforts of a regional health authority to engage actively with community members to develop more integrated and patient-centered primary health care delivery. We examine points of tension between providers and administrators engaged in the reform process and show how these are often expressed discursively as a binary opposition involving central and local interests. We offer a critical examination of this politics of scale and seek to unpack claims of hierarchy and power as a means to offer insight into health care reform processes more generally.